Transmigration Policy in the Context of Autonomy Era in East Kalimantan - Purwaningsih Purwaningsih; Dusadee Ayuwat; Jaggapan Cadchumsang (Iapa Proceedings Conference, 2019)
Transmigration in Indonesia is perceived as an important approach to improve welfare; however, this policy has also been a subject of criticism. Along with the enactment of the Regional Autonomy Law, the transmigration policy changed from centralized to decentralize. That is, the regional government has a large role in making decisions on the implementation of transmigration. The national transmigration program was rejected in several transmigration destinations in Indonesia. Nevertheless, transmigration is still recognized as one of the programs that can improve people's living standards and one of the ways to develop the region. This paper discusses the role of transmigration in the development process in East Kalimantan Province and various issues related to interactions between local communities and transmigration communities as migrants. The sources of data and information in this paper are reviews of various research reports, journal articles, books, and other supporting documents.